2022
DOI: 10.1002/nop2.1466
|View full text |Cite
|
Sign up to set email alerts
|

The simulation design in health and nursing: A scoping review

Abstract: Simulation is a teaching-learning strategy aligned with the perspective of an active methodology that, in the context of health and nursing education, enables students to develop skills and build knowledge in cognitive, procedural and attitudinal domains, preparing them for clinical practice (Kim et al., 2016;Lavoie et al., 2018;Onarici et al., 2021). It is associated with the development of skills necessary for nurses, which help in clinical judgement, decisionmaking and resolution of complex situations in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…In addition, considering that self‐confidence is the conviction that a person has of being able to do or accomplish something (Bandura, 1986; Lundberg, 2008) and is directly related to learning and clinical decision‐making (Fry & MacGregor, 2014; Groom et al, 2014; Oliveira Silva, Fonseca, et al, 2022; Oliveira Silva, Oliveira, et al,2022), understanding aspects of simulation design that best impact this competence can help in the elaboration of SBL for the best achievement of learning outcomes, consequently, impacting on the training of better qualified nurses. In this study, we adopted the recommendation of O'Donnell et al (2014) to treat self‐confidence and self‐efficacy as synonymous; thus, to both concepts we used the term self‐confidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, considering that self‐confidence is the conviction that a person has of being able to do or accomplish something (Bandura, 1986; Lundberg, 2008) and is directly related to learning and clinical decision‐making (Fry & MacGregor, 2014; Groom et al, 2014; Oliveira Silva, Fonseca, et al, 2022; Oliveira Silva, Oliveira, et al,2022), understanding aspects of simulation design that best impact this competence can help in the elaboration of SBL for the best achievement of learning outcomes, consequently, impacting on the training of better qualified nurses. In this study, we adopted the recommendation of O'Donnell et al (2014) to treat self‐confidence and self‐efficacy as synonymous; thus, to both concepts we used the term self‐confidence.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this framework, a scoping review identified three major groups of simulation design components (structural, methodological and theoretical‐pedagogical) (Oliveira Silva, Fonseca, et al, 2022; Oliveira Silva, Oliveira, et al,2022), so the focus of this systematic review is to identify the influence of structural components, such as the presence of prebriefing and debriefing, duration, modality, fidelity and type of simulator on stress, anxiety and self‐confidence outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation-based education approaches, which may include simulationbased assessment as a component, exhibit a high degree of variability [23], but there is a lack of consistency in how clinical reasoning is incorporated into these approaches for assessment purposes [17]. Although Silva et al reviewed 26 studies on simulation design components as a teaching-learning strategy, they did not focus on simulationbased assessment for evaluating clinical reasoning in students [24]. While Sommers, Brentnall et al, and Macauley et al reviewed tools available for measuring clinical reasoning [7,25,26], a comprehensive review is still needed to identify the design elements for simulation-based assessment of clinical reasoning in nursing students and build on previous literature.…”
Section: Introductionmentioning
confidence: 99%